Real-world assessment of treatment multiple myeloma patients on the example of one hematology center - A. S. Luchinin; N. V. Minaeva (Izdatelstvo OKI, 2023)
Relevance. Despite significant improvements in therapeutic options, patients with multiple myeloma (MM) experience a series of remissions and relapses requiring further lines of therapy, which requires the prescription of new lines of therapy. Methods. We analyzed the types and outcomes of treatment, attrition rates (AR) - the proportion of patients who dropped out of program therapy, and refractoriness to different lines of therapy (LOT) in 447 patients with MM between 2010 and 2022. Resalts. The AR was 17% between LOT-1 and LOT-2, 15% between LOT-2 and LOT-3, and 25% between LOT-3 and LOT- 4. In multivariate regression analysis, only high MM risk significantly increased AR risk. Each new progression of MM increased the number of patients with refractory to bortezomib, lenalidomide, or daratumumab. After LOT-1, LOT-2, and LOT-6%, 26%, and 53% of patients were double-refractory, respectively, and 54% were triple-refractory. Bortezomib- or lenalidomide-refractory patients had a 2.6-fold lower chance of achieving a very good partial response or better (VGPR+). From LOT-1 to LOT-4, the overall response rate and VGPR+ decreased from 74% and 53% to 25% and 15%, respectively. Overall survival (OS) in the entire population was 7.6 years, with an actuarial 5-year OS of 67% and a 10-year OS of 44%. The median of progression-free survival (PFS) was 20 months on LOT-1, 19 months on LOT-2, and 7 months on LOT-3, and the actuarial 5-year PFS was 25%, 18%, and 10%, respectively. Conclusions: In this regard, we observe a continuing trend in the use of cisplatin-containing "rescue" chemotherapy regimens, especially in patients with an aggressive course, including extramedullary forms of MM. These patients could be candidates for bispecific antibody therapy and CAR T-cell therapy, but these options are not yet available in Russia.